Insights, attitudes, and perceptions about asthma and its treatment: findings from a multinational survey of patients from Latin America - Maspero, Jorge F.; Jardim, José R.; Aranda, Alvaro; Tassinari C., Paolo; González Díaz, Sandra Nora; Sansores, Raul H.; Moreno Cantu, Jorge J.; Fish, James E. (2013)
Background: In 2011 the Latin America Asthma Insight and Management (LA AIM) survey explored the realities of living with asthma. We investigated perception, knowledge, and attitudes related to asthma among Latin American asthma patients. Methods: Asthma patients aged ≥12 years from four Latin American countries (Argentina, Brazil, Mexico, Venezuela) and the Commonwealth of Puerto Rico responded to questions during face-to-face interviews. A sample size of 2,169 patients (approximately 400 patients/location) provided an accurate representation of asthma patients’ opinions. Questions probed respondents’ views on topics such as levels of asthma control, frequency and duration of exacerbations, and current and recent use of asthma medications. Results: A total of 2,169 adults or parents of children with asthma participated in the LA AIM survey. At least 20% of respondents experienced symptoms every day or night or most days or nights. Although 60% reported their disease as well or completely controlled, only 8% met guideline criteria for well-controlled asthma. 47% of respondents reported episodes when their asthma symptoms were more frequent or severe than normal, and 44% reported seeking acute care for asthma in the past year. Asthma patients in Latin America overestimated their degree of asthma control. Conclusions: The LA AIM survey demonstrated the discrepancy between patient perception of asthma control and guideline-mandated criteria. Additional education is required to teach patients that, by more closely following asthma management strategies outlined by current guidelines more patients can achieve adequate asthma control.